Biogeochemical characteristics of sediment cores from a land – shore transect in the Teshekpuk Lake Region in Arctic Alaska, 2022 - Giest, Frieda; Jenrich, Maren; Grosse, Guido; Jones, Benjamin; Mangelsdorf, Kai; Windirsch, Torben; Strauss, Jens (PANGAEA, 2024)
This dataset describes six sediment cores (12 - 219 cm length) from different landscape features in a coastal permafrost thermokarst affected landscape in the Theshekpuk Lake region in Arctic Alaska. They are located in a transect from inland to coast, to describes the transitional dynamics between terrestrial and marine permafrost and thermokarst. The cores were drilled during the Perma-X Lagoon expedition in April 2022. The three unfrozen cores from a marine (MAR, 12 cm length), an intact lagoon (LAG, 31 cm length) and a thermokarst lake (TKL, 50 cm length) site, were all sampled using a Push Corer. The three frozen cores, including upland permafrost (UPL, 203 cm length), drained thermokarst lake basin (DLB, 219 cm length) and semi-drained lagoon (SDLAG, 183 cm length) deposits, were drilled using a SIPRE Corer. The biogeochemical analysis included subsamples taken in intervals of 5–10 cm along the cores. Parameters included total carbon (TC) [wt%], total organic carbon (TOC) [wt%], total nitrogen (TN) [wt%], TOC/TN ratio, δ¹³C [‰ vs. VPDB] , δ¹⁵N [‰ vs. air raw], TOC density (TOCvol) [kg/m³], and mercury (Hg) [µg/kg].
Keywords: Biomarker; coastal thermokarst; land-ocean transition; Organic carbon; Permafrost; Teshekpuk Lake